2010
DOI: 10.3399/bjgp10x483959
|View full text |Cite
|
Sign up to set email alerts
|

Place of death for the ‘oldest old’: ≥85-year-olds in the CC75C population-based cohort

Abstract: Deaths are rising fastest among the oldest old but data on their transitions in place of care at the end of life are scarce. AimTo examine the place of residence or care of ≥85 yearolds less than a year before death, and their place of death, and to map individual changes between the two. Design of studyPopulation-based cohort study. SettingCambridge City over-75s Cohort (CC75C) study, UK. MethodRetrospective analysis of prospective data from males and females aged ≥85 years at death who died within a year of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 33 publications
1
37
0
1
Order By: Relevance
“…In the UK, there is a perception that residents of nursing homes are still sent into acute hospitals to die, 45 and the probability of readmission to hospital within a short period of discharge is considerably higher for nursing home residents. [46][47][48] Analysis of data from the Cambridge City Over-75s Cohort Study 49 found that 15% of deaths in acute hospitals were from (predominantly residential) care homes. The more recent introduction of initiatives to improve end-of-life care in the care-home sector may lead to future changes.…”
Section: Transitions For Care-home Residentsmentioning
confidence: 99%
“…In the UK, there is a perception that residents of nursing homes are still sent into acute hospitals to die, 45 and the probability of readmission to hospital within a short period of discharge is considerably higher for nursing home residents. [46][47][48] Analysis of data from the Cambridge City Over-75s Cohort Study 49 found that 15% of deaths in acute hospitals were from (predominantly residential) care homes. The more recent introduction of initiatives to improve end-of-life care in the care-home sector may lead to future changes.…”
Section: Transitions For Care-home Residentsmentioning
confidence: 99%
“…Moreover, policy changes during the period of the study , such as closure of long-stay wards, may have influenced care options available; however, we have previously compared CC75C study findings to national statistics and found comparable trends in place of death. 18 The study had no access to medical records that might clarify reasons for transitions and their proximity to death.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Clinical diagnostic assessments, following the Cambridge Mental Disorders of the Elderly Examination (CAMDEX), 18 were conducted by old age psychiatrists in sub-samples of participants. Additionally, clinical diagnosis of dementia at death was made by at least two clinicians experienced in old age psychiatry according to the American Psychiatric Association's criteria (Diagnostic and Statistical Manual of Mental Disorders (4th ed.…”
Section: Dementia Statusmentioning
confidence: 99%
“…Although this study did not identify the institutionalised population, only about 3% of the sample reported moving to institutions in the previous two years [23].…”
Section: Strengths and Limitationsmentioning
confidence: 89%